Probiotic Properties of a Spaceflight-induced Mutant Lactobacillus Plant- arum SS18-50 in Mice - Wang, Dan; Zhang, Tiehua; Hao, Hongwei; Zhang, Hongxing; Ye, Haiqing; Zhao, Changhui (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Probiotics are a group of bacteria that play a critical role in intestinal microbiota homeostasis and may help adjunctively treat certain diseases like metabolic and immune disorders. Objective: We recently generated a space-flight mutated Lactobacillus plantarum SS18-50 with good in vitro probiotic characteristics. In the current research, we designed two in vivo experiments to evaluate whether L. plantarum SS18-50 had the ability to increase beneficial gut bacteria, regulate oxidative status and ameliorate inflammation in mice. Methods: Experiments I: the ICR mice were gavaged with L. plantarum SS18-50 or its wild type L. plantarum GS18 at 107 or 109 CFU/kg BW daily for one month, during which the body weight was recorded weekly. The feces were collected to determine the abundance of two main beneficial bacterial groups including Lactobacillus and Bifidobacterium by selective culturing, while the total triglycerides and cholesterols in sera were determined using commercial kits. Experiment II: the mice were gavaged with loperamide hydrochloride (Lop) to develop oxidative stress and inflammation phenotypes. At the same time, the experimental mice were gavaged with L. plantarum SS18-50 or wild type L. plantarum GS18 at 107 or 109 CFU/kg BW daily for one month. At the end of the experiment, oxidative indicators (SOD and MDA) and inflammatory cytokines (IL-17A and IL-10) were measured by commercial kits. Results: Results showed that L. plantarum SS18-50 increased the abundance of Lactobacillus and Bifidobacterium in mice after one month’s administration. L. plantarum SS18-50 also showed the anti-oxidant activity by increasing SOD and decreasing MDA and exerted the anti-inflammatory effect by increasing IL-10 and decreasing IL-17A in Lop treated mice. Both the wild type stain and the space mutant had such biomedical effects, but L. plantarum SS18-50 was better in increasing gut beneficial bacteria and oxidative regulation than the wild type (P<0.05). Conclusion: We conclude that L. plantarum SS18-50 has a great potential to serve as a dietary functional probiotic supplement and/or adjunctive treatment strategy.
Keywords: inflammatory cytokines